Factors influence domestic senior tourism in Malaysia - Chong, Zi Cheng; Leong, Mun Heng (2023)
Senior is a potential population that can contribute to the performance of various industries, including tourism because of global demographic change. As a country suffering from demographic changes, Malaysia should place more emphasis on senior tourism to boost the country's economy. The purpose of this study is to identify the destination attributes that influence the travel decisions of senior in Malaysia. It is hoped that the Malaysian tourism industry will expand its market into senior tourism by recognizing the attributes of the destinations that senior tourists tend to visit. The results of this study showed that, Complementary Services and Entrance Fee has significance relationship with senior tourism in Malaysia.